Nano-sized Ce-substituted hexagonal Co2–Y ferrite; a valuable catalyst for heterogeneous reduction of toxic nitro-organic pollutants. Issue 24 (15th December 2022) - Suthar, Mukesh; Srivastava, Avinash K.; Sharma, Charu; Joshi, Raj K.; Roy, P.K.
Abstract: This paper describes the synthesis of Ce-substituted Y-type barium hexaferrites (Co2 –Y) {Ba2 Co2 Fe12-x Cex O22 (0 ≤ x ≥ 0.30)} through the sol-gel auto-combustion route and its suitability as a heterogeneous catalyst for the reduction of nitroaromatic-compounds, one of the significant water contaminants. The synthesized nanocrystalline hexaferrite powders were characterized using XRD, FTIR, BET, SEM, and VSM. Furthermore, the catalytic functioning of the Co2 –Y hexaferrite powder was evaluated based on the isolated yield of aniline in the reaction product through column chromatography. It was found that 100 mg pure Co2 –Y hexaferrite samples could provide complete conversion of nitrobenzene and 65% selectivity of aniline within the water as a solvent and two mmol of reducing agent, hydrated hydrazine (N2 H2 .H2 O), at 100 °C for 12 h. The influence of Ce substitution at the iron site for the aniline selectivity was also investigated in optimized situations. In comparison with pure Co2 –Y hexaferrite, the catalytic efficiency was considerably enriched in all substituted samples and obtained its extreme performance (73% selectivity of aniline) with Ba2 Co2 Fe11.80 Ce0.20 O22 ferrite. The enriched performance was explained with the help of surface chemistry using the XPS & BET analysis for these samples. The as-prepared catalysts were magnetically-separable and recycled for five subsequent trials without any significant losses of catalytic performance. This catalyst may be convenient to be adopted for industrial applications due to its ease of synthesis, extraordinary stability, superior catalytic competence, and cost-effectiveness.